The Role of Guidance and Counseling Teachers in Addressing the Impact of Bullying in Schools (Case Study at SMP Negeri 1 Balongan) - Ismatul Lu'lu (Journal Of Psychology, Counseling And Education, 2025)
Bullying can generally have a negative impact, both on the victim, the perpetrator, and those who witness it. There needs to be a role for guidance and counseling teachers to overcome bullying. This research aims to find out the impact of bullying and the role of guidance and counseling teachers in dealing with bullying. The case study that is the object of research is SMPN 1 Balongan Indramayu. The type of research used is qualitative, with a case study method. The results of research show that the impact on victims of bullying is feeling lonely, depressed, social withdrawal, low self-esteem, low levels of social competence, complaints about physical health, running away from home, and decreased academic performance, adjustment bad social situation where the victim feels afraid of going to school, even doesn't want to go to school, feels worthless, suicidal, etc. Meanwhile, the role of the guidance and counseling teacher at SMPN 1 Balongan is to analyze the case so that we know what action should be taken next, then give punishment to the perpetrator, provide services to the victim and perpetrator.